The Influence of Visionary Leadership Style and Work Environment on Employee Work Productivity - Sholihah, Dwi Shinta Rahmatus; Moh Heru Budi Santoso; Diah Ayu Novitasari; Nanto Purnomo (Formosa Journal of Applied Sciences, 2024)
MSMEs in Indonesia, especially in the food industry, are currently developing quite rapidly and are widely known by the Indonesian people. In order for a company's life cycle to continue and productivity to increase and achieve its goals, it requires a visionary leader and a good work environment. The purpose of this writing is to find out how the influence of the visionary leadership style and work environment in increasing employee work productivity at the Cake Shop Emde Cake Sarirejo. The writing method used is a quantitative method with a sample of 35 people, respondents obtained through distributing questionnaires. The sampling technique used was random sampling with data analysis tools via IBM SPSS Statistics 26. The results of this paper show that the variable visionary leadership style (X1) does not have a positive and significant effect on work productivity (Y) and the work environment (X2) has a positive and significant effect on work productivity (Y). significant on work productivity (Y).